Seasonal Changes in Total Lipid Content and Fatty acid Profiles of Ribbon Fish, Lepturacanthus savala (Cuvier, 1829) - Ramesh, R.; Chakraborty, S. K.; Venkateshwarlu, G. (Fishery Technology, 2025)
In order to evaluate the seasonal changes in nutritive value of ribbon fish, in relation to size, total lipid and fatty acid profiles of different sizes of ribbon fish, Lepturacanthus savala captured in different seasons were studied. Total lipid content was significantly (p<0.05) high in large sized ribbon fish captured during winter and lowest in medium size groups during post-monsoon season. A total of 37 fatty acids were identified by Gas Chromatography - Mass Spectrometry encompassing saturated, mono unsaturated, n-6, n-3 poly unsaturated and odd and branched chain fatty acids. The highest content of eicosapentaenoic acid (9.42%) and docosahexaenoic acid (33.16%) were found in the post-monsoon season. The high levels of n-3 PUFA (12.37 – 43.14%) and favourable n-3/n-6 PUFA ratio of 1.79 to 5.04 revealed nutritional significance of ribbon fish in human diet. The difference between small, medium and large groups of ribbon fishes of the respective season based on fatty acid composition was clearly established by principal component analysis.